Eksistensi Hukum Adat Dalam Penyelesaian Sengketa Tanahulayat Di Indonesia - Halida Zia (Universitas Muara Bungo, 2021)
In customary law, the highest land tenure rights are ulayat rights which are jointly owned by the Customary Law Community. Customary law communities are subject to and bound by customary law that they have mutually agreed upon. what is the position and existence of customary law in the development of national law? Constitutionally, the state recognizes and respects customary law and its traditional rights as long as there are indigenous peoples who preserve it. In the settlement of customary land disputes that occur in the territory of customary law communities, they are resolved by customary means. The concept of deliberation and consensus used by indigenous peoples later became the forerunner to the development of national law. Keywords: Existence, Dispute, Customary Land AbstrakDalam hukum adat, hak penguasaan atas tanah tertinggi adalah hak ulayat yang dimliki secara bersama oleh Masyarakat Hukum Adat (MHA). Masyarakat hukum adat tunduk dan terikat pada hukum adat yang telah mereka sepakati bersama. Namun bagaimana kedudukan dan eksistensi hukum adat dalam pembangunan hukum nasional? Secara konstitusional negara mengakui dan mengohrmati hukum adat serta hak-hak tradisonalnya sepanjang masih ada masyarakat hukum adat yang melestarikannya. Dalam penyelesaian sengketa tanah ulayat yang terjadi di wilayah masyarakat hukum adat diselesaikan dengan cara adat. Konsep musyawarah mufakat yang dipakai masyarakat hukum adat kemudian menjadi cikal bakal pembangunan hukum nasional. Kata Kunci: Eksistensi, Sengketa, Tanah Ulayat